2022
DOI: 10.1002/ajhb.23776
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric measures do not explain the 2D:4D ratio sexual dimorphism in 7‐year‐old children

Abstract: Objectives Digit ratio (2D:4D) might reflect prenatal testosterone exposure and has been used as a putative marker for androgen related outcomes. However, such associations might be inflicted by confounders. Application of 2D:4D in epidemiological research motivate identification of biological background determinants. We examined sex, anthropometric measures, and maternal factors as determinants of 2D:4D in Swedish 7‐year‐old children. Methods The study was embedded in the Swedish Environmental, Longitudinal, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…they reported that the ratio was shorter in boys than girls (24). The results of another study showed that the 2D:4D ratio is signi cantly different in the two sexes and is shorter in boys than in girls (25). Malas et al showed no statistically signi cant difference between boys and girls in terms of this ratio (26), which is consistent with the results of the present study.…”
Section: Discussionsupporting
confidence: 92%
“…they reported that the ratio was shorter in boys than girls (24). The results of another study showed that the 2D:4D ratio is signi cantly different in the two sexes and is shorter in boys than in girls (25). Malas et al showed no statistically signi cant difference between boys and girls in terms of this ratio (26), which is consistent with the results of the present study.…”
Section: Discussionsupporting
confidence: 92%
“…These data confirm the hypothesis of sexual dimorphism with respect to the 2D:4D ratio, which reflects the levels of embryonic sex steroids. Sexual dimorphism in relation to the 2D:4D ratio persists throughout life, although data concerning sexual differences in this ratio in childhood are less variable compared to data in adults (Knickmeyer et al, 2011;Mitsui et al, 2015;Jägetoft et al, 2022).…”
Section: Introductionmentioning
confidence: 91%
“…The ratio between length of the index and ring digit (2D:4D) has therefore been proposed to serve as a proxy marker for in utero androgen exposure. Several reviews and meta-analyses have shown that in most cases men and boys have lower values of this ratio than women and girls, suggesting that the gender difference in the 2D:4D ratio is determined by higher levels of androgens in male embryos compared to female (Hönekopp et al, 2007;Grimbos et al, 2010;Knickmeyer et al, 2011;Xu, Zheng, 2015;Swift-Gallant et al, 2020;Jägetoft et al, 2022). One study (Mitsui et al, 2015) showed gender differences in testosterone levels of umbilical cord blood samples, which were significantly higher in samples collected from males than those from females.…”
Section: Introductionmentioning
confidence: 99%
“…Another criticism towards ratios and 2D:4D in particular is that sexual dimorphism in 2D:4D might have aroused because of the basically size differences between two sexes. It is thought that sexual dimorphism in 2D:4D is mainly caused by the shift along the common allometric line (Kratochvíl & Flegr, 2009; but see Jägetoft et al, 2022). Van Dongen (2009) in his study revealed that the use of digit length as both dependent and independent variables can result in artificial correlations in FA studies.…”
Section: Introductonmentioning
confidence: 99%